2017
DOI: 10.1039/c6nr08045f
|View full text |Cite
|
Sign up to set email alerts
|

Spray-assisted alignment of Layer-by-Layer assembled silver nanowires: a general approach for the preparation of highly anisotropic nano-composite films

Abstract: The present article focuses on the build-up and the properties of oriented silver nanowire monolayer films and Layer-by-Layer assembled multilayer films. We describe the template-free oriented spray-assisted assembly of silver nanowires at solid/air-interfaces using Grazing Incidence Spraying, a simple and versatile approach that allows the formation of highly oriented thin films with a tunable density and in-plane orientation. Depending on the spraying conditions the nematic order parameter, which describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 57 publications
(43 reference statements)
1
89
0
Order By: Relevance
“…As more and more nanowires are deposited, the “free places” for new nanowires to interact with the PDMS substrate is limited, and the deposition rate reduces accordingly. As a result, the surface coverage reaches a plateau for longer coating times and this result is consistent with the other reports …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As more and more nanowires are deposited, the “free places” for new nanowires to interact with the PDMS substrate is limited, and the deposition rate reduces accordingly. As a result, the surface coverage reaches a plateau for longer coating times and this result is consistent with the other reports …”
Section: Resultssupporting
confidence: 93%
“…Some strategies such as rubbing, external field–assisted assembly, coassembly, bubble blowing, dip coating, printing, chemical bonding, strain‐release assembly, wrinkle‐assisted assembly, shear coating, and interface‐mediated assembly can lead to a single oriented layer. And some strategies including Langmuir–Blodgett technique, evaporation‐induced assembly, electrospinning, fluidic flow, spray coating, and brush coating can be repeated to form multilayered oriented structures. However, there are still some inherent limitations that severely restrict their applications as some of the above techniques require complicated process or specialized equipment such as additional transfer process, surface patterning, spraying nozzles, and special substrates, which limit the cost‐effective assembly of high‐density nanowires in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AgNWs can be orderly deposited on solid substrate by using the grazing incidence spraying method (scheme shown as Figure S3 in Supporting Information) . Using these ordered AgNWs (Figure S4 a) as templates, it is possible to prepare aligned APS line patterns, which could also be used for assembly of small molecules and nanoparticles, generating corresponding aligned line patterns (optical image of the assembled AuNPs was shown as Figure S4 b).…”
Section: Figurementioning
confidence: 99%
“…[37] These AuNPs patterns provide at unable plasmonic structure, which has potential applications in the fields of SERS sensing and nanophotonics.It has been reportedt hat AgNWsc an be orderly deposited on solid substrate by using the grazing incidence spraying method (scheme shown as Figure S3 in Supporting Information). [39][40][41] Using these ordered AgNWs (Figure S4 a) as templates, it is possible to prepare alignedA PS line patterns, which could also be used for assembly of small molecules and nanoparticles, generating corresponding aligned line patterns (opticali mage of the assembled AuNPs was shown as Figure S4 b). In addition, more complex molecular patterns could also be preparedb yc ontrolling the assembly of AgNWs.The assembled nanoparticle patterns could be used for SERS detection.…”
mentioning
confidence: 99%
“…However, processes requiring vacuum evaporation and RIE may be insufficiently cost‐effective and high‐throughput to manufacture Al WGPs. Bottom‐up approaches to fabricate WGPs have been attempted, such as colloidal assembly, metal‐containing block copolymers, and nanowire alignment . However, the limitations of the material selection and structural versatility caused unsatisfactory WGP performance.…”
Section: Introductionmentioning
confidence: 99%